Characterization of neurological disease progression in a canine model of CLN5 neuronal ceroid lipofuscinosis. Issue 4 (28th April 2022) - Meiman, Elizabeth J.; Kick, Grace Robinson; Jensen, Cheryl A.; Coates, Joan R.; Katz, Martin L.
Abstract: Golden Retriever dogs with a frameshift variant in CLN5 (c.934_935delAG) suffer from a progressive neurodegenerative disorder analogous to the CLN5 form of neuronal ceroid lipofuscinosis (NCL). Five littermate puppies homozygous for the deletion allele were identified prior to the onset of disease signs. Studies were performed to characterize the onset and progression of the disease in these dogs. Neurological signs that included restlessness, unwillingness to cooperate with the handlers, and proprioceptive deficits first became apparent at approximately 12 months of age. The neurological signs progressed over time and by 21 to 23 months of age included general proprioceptive ataxia, menace response deficits, aggressive behaviors, cerebellar ataxia, intention tremors, decreased visual tracking, seizures, cognitive decline, and impaired prehension. Due to the severity of these signs, the dogs were euthanized between 21 and 23 months of age. Magnetic resonance imaging revealed pronounced progressive global brain atrophy with a more than sevenfold increase in the volume of the ventricular system between 9.5 and 22.5 months of age. Accompanying this atrophy were pronounced accumulations of autofluorescent inclusions throughout the brain and spinal cord. Ultrastructurally, the contents of these inclusions were found to consist primarily of membrane‐like aggregates. Inclusions with similar fluorescence properties were present in cardiac muscle. Similar to other forms of NCL, the affected dogs had low plasma carnitine concentrations, suggesting impaired carnitine biosynthesis. These data on disease progression will be useful in future studies using the canine model for therapeutic intervention studies.